Preclinical Safety and Pharmacokinetics of Heat Stable Oxytocin in Sublingual Fast-Dissolving Tablet Formulation - Changcheng Zhu; Manjari Lal (MDPI AG, 2022)
The work reported here focuses on an evaluation of a novel heat stable formulation of a uterotonic peptide drug oxytocin involving stability testing under elevated temperatures and toxicokinetic response generated by sublingual (SL) administration in rabbits. The formulation was thermotolerant, maintaining the potency of oxytocin in the form of a fast-dissolving tablet at the end of 2-year storage at 30 °C/65% relative humidity with less than 5% loss in oxytocin content based on analytical high performance liquid chromatography (HPLC). The toxicokinetic results in rabbits showed that the fast-dissolving tablet was safe without any reactogenicity or toxicity associated with SL administration or the excipients present in the formulation. The SL route elicited rapid absorption of oxytocin in plasma within 5 min of administration although lower than intramuscular (IM) administration. IM resulted in area under the curve (AUC) values approximately 5 times higher than SL oxytocin. However, due to the limitations encountered during SL administration in an anesthetized rabbit model, the relevance of heat stable oxytocin formulation that has the flexibility to be adapted in different formats may warrant a human clinical study to determine whether therapeutically relevant plasma levels for treating postpartum hemorrhage can be generated via alternate non-injectable routes of administration.